Síntese de chalconas por condensação de Claisen Schmidt : um estudo da relação estrutura versus atividades biológicas - Souza, Gabriella Barroso (2019)
The diversity of neglected tropical diseases (NTDs) has become a major threat, causing millions of people to die annually reported by World Health Organization (WHO).Climate change, urbanization, the incorrect treatment of domestic and industrial wastes and the use of insecticides has been some of the factors that contribute to the occurrence of these diseases. The application of chemical compounds which present pharmacological potential activity has been shown as an efficient alternative for the treatment and prevention of several health problems. In this context, synthesized chalcones are considered promising molecules, once they have been widely used in the development of prototypes for the production of drugs, due to its range of biological activities. Aiming to contribute on the development of synthesized molecules and with the study structure versus activity of bioactive substances, this study performed the synthesis and characterization by spectroscopic and chromatographic techniques ten chalcones obtained by Claisen Schmidt condensation: (E)-1,3-diphenyl-prop-2-en-1-one (C-1), (E)-1-phenyl-3-(4-methoxyphenyl)-prop-2-en-1-one) (C-2), (E)-1-(4-methoxyphenyl)-3-phenyl-prop-2-en-1-one (C-3), (E)-1-(benzo[d]-[1,3]-dioxol-6-yl)-3-(4-methoxyphenyl)-prop-2-en-1-one (C-4), (E)-1-phenyl-3-α-naphthylprop-2-en-1-one (C-5), (E)-1-(4-methoxyphenyl)-3-α-naphthylprop-2-en-1-one (C-6), (E)-1,3-Bis-(4-methoxyphenyl)-prop-2-en-1-one (C-7), (E)-1-(benzo [d] -[1,3] dioxol-6-yl)-3-α-naphthylprop-2-en-1-one (C-8), (E)-1-(4-methoxyphenyl)-3-(2-furanyl) prop-2-en-1-one (C-9) and (E)-1-(benzo[d]-[1,3]dioxol-6-yl)-3-(2-furanyl)-prop-2-en-1-one (C-10), the last unpublished. The chalcones were subjected to larvicidal tests, anti-protozoal, antibacterial and antifungal activity. In all the tests, the biological activities of these substances associated to presence of the aromatic rings attached to the enone, their substituents and their respective ring positions.